2022
DOI: 10.1002/pra2.742
|View full text |Cite
|
Sign up to set email alerts
|

Academic Casualization, Precarity, and Information Practices: A Scoping Review

Abstract: In the first phase of a larger research project exploring the information practices of contract academic staff, a review of the wider literature around academic casualization was conducted. This research begins to address the need for greater understanding of the experiences of these workers in the information‐intensive environments of higher education. A scoping review methodology was applied, and both academic and grey literature from multiple disciplines was reviewed. The literature points to casualization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, despite the pervasiveness of these issues, a scoping review conducted as a preliminary phase of this research found relatively little empirical research exploring the perceptions and practices of contract academic staff (Willson, et al, 2022). In addition, despite the complexity of their information environments, researchers have not previously examined the information practices and workplace environments of this group.…”
Section: Higher Education Contextmentioning
confidence: 99%
“…However, despite the pervasiveness of these issues, a scoping review conducted as a preliminary phase of this research found relatively little empirical research exploring the perceptions and practices of contract academic staff (Willson, et al, 2022). In addition, despite the complexity of their information environments, researchers have not previously examined the information practices and workplace environments of this group.…”
Section: Higher Education Contextmentioning
confidence: 99%
“…As Calarco (2020:2) indicates “hiddenness perpetuates inequalities in grad school and in academia” where grad students from more privileged backgrounds tend to gain more rewards in academia since they have friends or family members who have been to grad school and can guide and help them uncover hidden curriculum. Information thus plays a critical role in eliminating educational and professional inequalities by supporting doctoral students and early career researchers to access key resources (Moore & Singley, 2019; Sloan & McPhee, 2013; Willson et al, 2022). Prior research has assessed information practices by non‐dominant groups, including students with underrepresented backgrounds, seeking information to (re)build social capital, support wellbeing, and improve positive learning experiences (Chang et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, while often still desiring tenure‐track appointments, CAS increasingly remain in such positions long‐term (Spina et al, 2022), shattering myths of such work as a steppingstone to full‐time employment, limiting their possibilities for advancement, and compounding the impacts on their personal lives. Despite increased attention in recent years, a scoping review conducted by the research team (Willson et al, 2022) found a dearth of empirical research and a lack of studies exploring the information practices of CAS. To address these gaps, this research addressed the following research questions: (1) How do CAS negotiate their information environments in order to situate themselves in their workplaces and career trajectories?…”
Section: Introductionmentioning
confidence: 99%